Methodological proposal for evaluating the transformation of urban microclimate in medium-sized cities: a case study in the urban mesh of the municipality of Paracatu, Minas Gerais - Santos, Arthur; Simionatto, Henzo (Ra’e Ga: o Espaço Geográfico em Análise, 2023)
This work aims to propose a methodological proposal for areas evaluated with potential for the formation of Urban Heat Islands (UHI). Satellite images were used to control surface temperature (Land Surface Temperature - LST) and the Normalized Difference Vegetation Index (NDVI) of the study area. They were also employed in the Annual Mapping of Land Cover and Land Use in Brazil. The city of Paracatu, Minas Gerais (MG) was chosen for application and validation of the proposed method. Images from LANDSAT-5 and 8 satellites were used, which initially underwent resampling and pixel standardization. Subsequently, LST and NDVI calculations were applied, and these data were compared with use and occupation. In general, it was possible to notice that, in the urban area of Paracatu, there was an increase in the average, minimum and maximum LST. The same space-spectral behavior occurred for the NDVI index, which are related to Land Use and Occupancy Changes (LULC). In relation to areas with potential formation of UHI, it was noted that, in the interval of 14 years, they tripled in the city, making it possible to relate the situation with urban expansion and the presence of new subdivisions in peripheral areas. It was also noted that areas with mitigation potential for UHIs were not planned, especially in the most populous neighborhood of the municipality. The results obtained were satisfactory and the proposed methodology can serve as a basis for municipal decision makers in relation to measures to mitigate urban microclimate.